STUDENTS’ COMPETENCE IN CRITICAL READING - Hardianti Diman; Naniek Jusnita; Suratman Dahlan; Abd. Halim Daud (Universitas Khairun, 2020)
The objectives of this research is to know students’ competence in critical reading at the fourth semester students of English Language Education Study Program, Khairun University consisting of 20 students who were selected by using purposive sampling technique. The researcher applied quantitative descriptive method and analyzed the data by using critical reading rubric. From the data analyzed, the data showed nine students was categorized good. Ten students was categorized fair and one students was categorized poor. The analysis of questions the data showed that students’ got highest average score 56 on the question number eigh as categorized fair. So, it can be concluded the students’ fourth semester of Khairun University Ternate have fair competence in critical reading.